(untitled) (Research, Society and Development, 2025)
Temporomandibular disorder (TMD) affects approximately 30–34% of the global population, with a higher prevalence in women (37.0%) compared with men (29.3%). It is considered one of the leading causes of chronic orofacial pain and negatively impacts essential functions such as chewing, speech, and overall quality of life. TMD presents a multifactorial etiology, involving biomechanical, emotional, and behavioral factors. Physical therapy has become an effective conservative approach, incorporating resources such as electrotherapy, manual therapy, therapeutic exercise, and postural reeducation. The aim of this study was to review recent scientific literature on physiotherapeutic approaches used in the management of TMD, highlighting their effectiveness in reducing pain and restoring function. A qualitative narrative review was conducted, including studies published between 2010 and 2025 and identified in databases such as SciELO, PubMed, PEDro, and LILACS. The findings show that physiotherapeutic interventions—including manual therapy, electrotherapy, therapeutic exercises, functional training, and postural training—contribute significantly to symptom relief and functional recovery, especially when integrated into an interdisciplinary treatment approach. In conclusion, the role of the physical therapist is essential in the management of TMD, and the standardization and continuous updating of evidence-based clinical protocols are indispensable for improving therapeutic outcomes.